New Progress in the Integrated Treatment of Traditional Chinese and Western Medicine for Recurrent Aphthous Ulcer in the Oral Cavity - Wang, Dan (International Journal of Public Health and Medical Research, 2024)
Recurrent aphthous ulcer in the oral cavity is a common oral mucosal disease with periodic, recurrent, and self-limiting characteristics. This article aims to explore the new progress of integrated traditional Chinese and Western medicine in the treatment of recurrent aphthous ulcers in the oral cavity. Through a comprehensive analysis of relevant research, the advantages and mechanisms of integrated traditional Chinese and Western medicine in improving efficacy, reducing symptoms, and reducing recurrence rates are elaborated, providing reference for clinical treatment.